The effectiveness of cardiac resynchronization therapy in patients with chronic heart failure of various origin depending on the structural myocardial injury in cardiac magnetic resonance imaging - O. V. Stukalova; N. A. Mironova; M. D. Utsumueva; S. Yu. Kashtanova; E. A. Butorova; V. N. Shitov; G. S. Tarasovsky; S. P. Golitsyn; S. K. Ternovoy (Российский кардиологический журнал, 2019)
Aim. To assess the effect of the size and pattern of myocardial structural injury, determined by magnetic resonance imaging (MRI), on response to cardiac resynchronization therapy (CRT) in patients with ischemic and non-ischemic heart failure (HF).Material and methods. Forty seven patients with ischemic and non-ischemic HF (age 62,3±8,9 years (mean±SD), 44,6% females and 55,4% males), left ventricle (LV) ejection fraction <35%, QRS complex >130 ms, and sinus rhythm were included in the study. Late-gadolinium enhancement-cardiovascular magnetic resonance (LGE-CMR) was undertaken to evaluate myocardial scar prior to CRT devices implantation. All CMR analysis was performed on CVI42 software. According to signal intensity, fibrosis zone and “grey zone” were defined for quantitative analysis (proportion and mass) of injury. Scar zone included fibrosis zone and “grey zone”. Scar location was assessed using a 16-segmentLV model. Response was defined as a reduction inLV end systolic volume of >15% at 6 months follow-up and HF functional class amelioration.Results. In nonresponse group there was significantly higher proportion and mass of total scar (median 4% [2,5; 19] vs 24% [7; 44], p=0,012,6 g [3,5; 32,5] vs41 g [8; 86], p=0,013)), fibrosis zone (median 0% [0; 3,5] vs 8% [0; 19], p=0,01,0 g [0; 6] vs14 g [0; 34], p=0,014) and “grey zone” (4% [2,5; 15] vs 15% [7; 23], p=0,018,6 g [3,5; 27,5] vs23 g [8; 39], p=0,25). Response proportion in non-ischemic HF patients was higher than in ischemic HF patients (78,5% vs 28,5%, p<0,01). Response to CRT was less in patients with posterolateral scar, more specifically in segments 4,5,6,11,12,15,16 (p<0,05). CRT response in ischemic HF did not depend on size of myocardial structural injury, but depend on scar localization. Lateral scar was associated with poor response. In non-ischemic HF, proportion and mass of fibrosis zone was less in responder group (median 0% [0; 1] vs 8,5% [0; 11], p<0,05,0 g [0; 1] vs14,5 g [0; 22], p<0,05.Conclusion. Response to CRT is significantly higher in non-ischemic than in ischemic HF patients. Nonresponse to CRT is associated with posterolateral scar, regardless of the HF origin. In patients with non-ischemic HF, size of fibrosis zone is lower in the responder group. In patients with ischemic HF, size ofLV structural injury does not affect the CRT efficiency, but lateral scar is associated with CRT nonresponse.